BAMBU PETUNG AS INSPIRATION FOR MAKING CASUAL CLOTHES WITH A KIMONO SILHOUETTE - Nur'aini, Rifa; Sugiyem, Sugiyem (Home Economics Journal, 2025)
Batik is an ancestral cultural heritage that combines technology and art with a lengthy production process involving multiple stages. However, interest in classic batik among teenagers and women in their 20s has declined, as its motifs and colors are often perceived as outdated and unfashionable. This study aims to develop casual fashion designs inspired by bamboo to create modern batik motifs. Using a Research and Development (R&D) method, the study employed public response questionnaires to identify design preferences among young women. The results reveal a modern, fashionable, and aesthetically pleasing design that remains comfortable. The combination of kimono and culottes was found to enhance comfort and appeal. Expert evaluations yielded average scores of 47.5 for the motif, 48 for batik quality, and 32 for casual design. Meanwhile, responses from 51 participants indicated that the most appreciated aspects were motif elements, the meaning behind the motifs, and color combinations, followed by motif placement on casual fashion silhouettes and design details. These findings suggest that blending traditional elements (batik, kimono) with modern styles (culottes, casual fashion) is well-received by the target market in terms of both aesthetics and functionality. Future research should explore more diverse color combinations and garment details while maintaining the kimono-culotte concept to broaden the market reach.